Injury epidemiology in professional ballet: a five-season prospective study of 1596 medical attention injuries and 543 time-loss injuries - Mattiussi, A. M.; Shaw, J. W.; Williams, S.; Price, P. D. B.; Brown, D. D.; Cohen, D. D.; Clark, R.; Kelly, S.; Retter, G.; Pedlar, C.; Tallent, J. (British Journal of Sports Medicine, 2021)
Objectives: To describe the incidence rate, severity, burden and aetiology of medical attention and time-loss injuries across five consecutive seasons at a professional ballet company. Methods: Medical attention injuries, time-loss injuries and dance exposure hours of 123 professional ballet dancers (women: n=66, age: 28.0±8.3 years; men: n=57, age: 27.9±8.5 years) were prospectively recorded between the 2015/2016 and 2019/2020 seasons. Results: The incidence rate (per 1000 hours) of medical attention injury was 3.9 (95% CI 3.3 to 4.4) for women and 3.1 (95% CI 2.6 to 3.5) for men. The incidence rate (per 1000 hours) of time-loss injury was 1.2 (95% CI 1.0 to 1.5) for women and 1.1 (95% CI 0.9 to 1.3) for men. First Soloists and Principals experienced between 2.0-2.2 additional medical attention injuries per 1000 hours and 0.9-1.1 additional time-loss injuries per 1000 hours compared with Apprentices (p=0.025). Further, intraseason differences were observed in medical attention, but not time-loss, injury incidence rates with the highest incidence rates in early (August and September) and late (June) season months. Thirty-five per cent of time-loss injuries resulted in over 28 days of modified dance training. A greater percentage of time-loss injuries were classified as overuse (women: 50%; men: 51%) compared with traumatic (women: 40%; men: 41%). Conclusion: This is the first study to report the incidence rate of medical attention and time-loss injuries in professional ballet dancers. Incidence rates differed across company ranks and months, which may inform targeted injury prevention strategies.No data are available.